Leuconostoc lactis and Staphylococcus nepalensis Bacteremia, Japan - Satoshi Hosoya (Emerging Infectious Diseases, 2020)
Leuconostoc lactis is a glycopeptide-resistant, gram-positive, facultative anaerobic coccus isolated from dairy products, whereas Staphylococcus nepalensis is coagulase-negative coccus that has not been identified as human pathogen. We report an instructive case of L. lactis and S. nepalensis bacteremia in a 71-year-old man who experienced Boerhaave syndrome after a meal.